The Global Gender Distortions Index (GGDI): An application to Indian states - Pinelopi K. Goldberg; Somik V. Lall; Meet Mehta; Michael Peters; Aishwarya Lakshmi Ratan (Yale University, Economic Growth Center, 2024)
The extent to which women participate in the labor market and have access to formal employment differs greatly across Indian states. In this paper we build on the methodology developed by Hsieh, Hurst, Jones, and Klenow (2019) to estimate the productivity consequences of such differences. Using rich microdata on occupational sorting and earnings, our theory allows to separately identify labor demand distortions (e.g., discrimination in hiring for formal jobs) from labor supply distortions (e.g., frictions that discourage women's labor force participation). We find that both demand distortions and supply distortions are negatively related to state-level economic development. Equalizing distortions across Indian states could raise state-level productivity by up to 15%.
Keywords: 330